Helium escaping from the atmosphere of a nearby rocky exoplanet orbiting in a habitable zone - Collin Cherubim; Shreyas Vissapragada; Tim Cunningham; Annabella G. Meech; David Charbonneau; Robin Wordsworth; Aaron Householder; Johanna Teske; Leonardo A. dos Santos; Nicole L. Wallack; William Misener; Zifan Lin; et al. (Science, 2026)
Observations of highly irradiated gas giant exoplanets have shown helium escaping from their atmospheres. There is limited evidence for atmospheres on rocky exoplanets, perhaps because they have already escaped. We report near-infrared spectroscopic observations of LHS 1140b, a rocky exoplanet that orbits in the habitable zone of a nearby low-mass star. The transit spectra show absorption by helium escaping from the planet’s atmosphere. Helium absorption is detected in 2024 but not in 2025, indicating time-variable atmospheric escape. We interpret these results as indicating an upper atmosphere dominated by helium and depleted in hydrogen, with other volatile species trapped at lower altitudes, consistent with atmospheric fractionation models. No helium absorption is detected for LHS 1140c, a smaller and more strongly irradiated exoplanet in the same system.